PROSPEKSI ENDAPAN BATUBARA DIDAERAH SENANING DAN SEKITARNYA,KABUPATEN SINTANG, KALIMANTAN BARAT - Harry Pramudito; Denny S Djohor (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2017)
The need for coal as fuel in the industrial field still plays an important role, as evidenced by the increasing demand for coal with certain quality to date. The purpose of this research are: To know the availability of coal in the research area, to know the direction of coal deployment and its thickness, to know the prospect of coal in the research area. The expected target is to know the prospect of coal in the research area. By using survey method observation and observation field then correlation and analysis based on USGS method.According to Setyana, 2005 regional geology of research areas into the Ketungau Basin, so that the sedimentary rocks in it have the same deposition history on the Basin. The formation of a coal carrier is a formation of mites. Coal outcrops are very rare in research areas with average stance and slope N 45oE/12o. From the results of the correlation of several test wells and the analysis of outcrop data, the coal in the study area has a thickness between 5cm - 80cm, in some places in the form of lensis and in some other places in the form of ribbon.